Methane–Coal Dust Mixed Explosion in Transversal Pipe Networks. Issue 10 (27th July 2021) - Niu, Yihui; Zhang, Leilin; Shi, Biming; Yang, Qianyi; Zhong, Zhen
ABSTRACT: To study the phenomenon of sedimentary coal dust being lifted by impact airflow after the underground methane explosion participated in the explosion, a transversal pipe network system of gas– coal dust explosion was set up in the laboratory. The set-up was used in an experimental study on overpressure evolution laws and flame propagation characteristics of sedimentary coal dust with five different particle sizes in the explosion in the transversal pipe network. Results indicated that the parallel branches, peak overpressure, and flame propagation speed presented gradually declining tendency as the distance from ignition point increased, the flame duration was first lengthened and then shortened, and the maximum distance of flame propagation is 8.5m. Among the transversal branch of the pipe, network formed a high-pressure zone under the superposition effect of pressure waves from opposite directions, but no optical signal was detected. Maximum explosion overpressure first tended to increase and then decline as the particle size of sedimentary coal dust increased. For coal dust with a particle size of 64– 106 μm, peak overpressure and flame propagation speed were the maximum, being 1.266 MPa and 425.17 m/s, respectively. The results provided a theoretical guidance for the suppression of explosions, the prevention of disasters, and control of methane– coal dust mixed explosions in coal mines.